Iterative algorithms based on the viscosity approximation method for equilibrium and constrained convex minimization problem - Tian, Ming; Liu, Lei (Fixed point theory and algorithms for sciences and engineering, 2012)
The gradient-projection algorithm (GPA) plays an important role in solving constrained convex minimization problems. Based on the viscosity approximation method, we combine the GPA and averaged mapping approach to propose implicit and explicit composite iterative algorithms for finding a common solution of an equilibrium and a constrained convex minimization problem for the first time in this paper. Under suitable conditions, strong convergence theorems are obtained. MSC: 46N10, 47J20, 74G60.